The Realization of Lexical Bundle Structures and Functions in English Education Journal - Ferdika Wijaya Kusuma; Dwi Rukmini; Abdurrachman Faridi (English Education Journal, 2022)
Discourse is unquestionably constructed with what is presumed as lexical bundle, and in each genre, it idiosyncratically occurs. Thus, the identification of idiosyncrasy of a particular genre would be beneficial for some parties in forming a decent and appropriate discourse. This study aims to explain the construction and function of lexical bundles including bundles which do not fit to theories used in this study. This is corpus-based research. Four-word bundles extracted from 50 chosen articles in EEJ using Antcont 3.5.8 were analyzed accordance with the structure of lexical bundle theory by Biber et. al (1999) and the function of lexical bundle theory by Conrad & Biber (2005). The result showed that (1) the constructions realized in the genre are noun phrase with of-phrase fragment, anticipatory it + verb phrase/adjective phrase, (Verb phrase +) that-clause fragment, copula be + noun phrase/adjective phrase, other prepositional phrase, and prepositional phrase with embedded of-phrase fragment. (2) The functions realized are stance expression, referential expression, and discourse organizer. (3) The excluded structures realized are noun phrase with gerund as modifier and noun phrase with and conjunction in between. (4) The excluded function is to express an entity. This research provides educational department academics variety of expressions for their academic discourse organizations and other researchers new findings concerning other lexical bundles’s structures and functions apart from the theorists.